Grenada : Interim Poverty Reduction Strategy Paper; Joint Staff Advisory Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper reviews the joint advice of the staffs of the World Bank and the International Monetary Fund on the Interim Poverty Reduction Strategy Paper (I-PRSP). This I-PRSP outlines the main areas envisaged to reduce poverty and the measures for the implementation of the full Poverty Reduction Strategy (PRS). The full PRSP could improve on the I-PRSP by building on its strength of inclusiveness, strengthening its policy focus, including the link between policy and resource use, and elaborating a clear framework for the coordination and monitoring of the strategy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet